They arrived and don’t stop coming: an update on the distribution of exotic ants (Hymenoptera, Formicidae) in continental Ecuador - Jefferson Salazar-Basurto; Adrián Troya; Francisco Romero; Alexander L. Wild; Alex Pazmiño-Palomino (Check List, 2023)
We present an updated list of introduced ants to continental Ecuador, and compile records of occurrence, as well as map the distribution of 15 exotic species. We analyzed specimens in entomological collections and data from AntWeb, GBIF and iNaturalist. Among these, we add two new records for the country: Cardiocondyla mauritanica Forel, 1980 and Pheidole megacephala (Fabricius, 1793). The former is also the first record for South America, while the finding of the latter shows how little we know about introduced tramp ants. In addition, we add site records for nine species: Cardiocondyla emeryi Forel, 1881, Cardiocondyla minutior Forel, 1899, Cardiocondyla wroughtonii (Forel, 1890), Linepithema humile (Mayr, 1868), Monomorium floricola (Jerdon, 1851), Monomorium pharaonis (Linnaeus, 1758), Paratrechina longicornis (Latreille, 1802), Tapinoma melanocephalum (Fabricius, 1793), and Tetramorium bicarinatum (Nylander, 1846). Based on our previous fieldwork observations, it appears that our understanding of exotic species richness is still in its early stages.